Effectiveness, safety and tolerability of a complex homeopathic medicinal product in the prevention of recurrent acute upper respiratory tract infections in children: a multicenter, open, comparative, randomized, controlled clinical trial. Issue 1 (December 2016) - Jong, Miek; Buskin, Stephen; Ilyenko, Lydia; Kholodova, Irina; Burkart, Julia; Weber, Stephan; Keller, Thomas; Klement, Petra
Abstract Background The present study was initiated to investigate the effectiveness, safety and tolerability of complex homeopathic CalSuli-4-02 tablets on prevention of recurrent acute upper respiratory tract infections (URTIs) in children, in comparison to another complex homeopathic product. Methods The study was designed as a prospective, multicenter, randomized, open, clinical trial with two parallel treatment groups at four outpatient pediatric clinics in Russia. Children aged ≤ 6 years with susceptibility to acute URTIs (≥ three occasions during the last 6 months) were randomized to receive either CalSuli-4-02 or a comparator homeopathic product (control group) for 3 weeks. Primary outcome was the frequency of acute URTIs after 3 and 6 months post-treatment follow-up. Secondary endpoints were changes in complaints and symptoms (total and individual scores), treatment satisfaction, antibiotic use, safety and tolerability. Results The intention-to-treat analysis involved 200 children (CalSuli-4-02:N  = 99, Control:N  = 101). In both treatment groups, the median number of acute URTIs was one for 3 months and two, respectively, for the full 6 months post-treatment (Relative Risk: 0.86 (95 %-CI: 0.72–1.03), p = 0.1099 ). Seasons had no influence on the outcome. At the end of study, CalSuli-4-02 had overall higher odds of getting lower complaints severity total score (Odds ratio: 1.99 (95 %-CI: 1.31–3.02), p = 0.0012 ) and showing symptom improvement (Odds ratio: 1.93 (95 %-CI: 1.25–3.00), p = 0.0033 ). Specifically, the complaint "appetite disorder" and the symptom "child's activities" significantly improved more in the CalSuli-4-02 group (p = 0.0135 andp = 0.0063, respectively). Antibiotic use was decreased in both treatment groups at the study end. Overall assessment for satisfaction with and tolerability of treatment was higher with CalSuli-4-02. A low number of non-serious adverse drug reactions was reported (CalSuli-4-02:N  = 4, Control:N  = 1). Conclusions Both complex homeopathic products led to a comparable reduction of URTIs. In the CalSuli-4-02 group, significantly less URTI-related complaints and symptoms and higher treatment satisfaction and tolerability were detected. The observation that the use of antibiotics was reduced upon treatment with the complex homeopathic medications, without the occurrence of complications, is interesting and warrants further investigations on the potential of CalSuli-4-02 as an antibiotic sparing option. Clinical trial registration number Roszdravnadzor: Study No164–563